Réponses

Meilleure réponse !
2014-02-24T13:51:13+01:00
A = 3/7 x (7/3 - 5/6)
A = 3/7 x (7 x 2 / 3 x 2 - 5/6)
A = 3/7 x (14/6 - 5/6)
A = 3/7 x 9/6
A = 27/42
A = 3 x 9 / 3 x 14
A = 9/14

B = 3/7 x 7/3 - 5/6
B = 21/21 - 5/6
B = 21 x 2 / 21 x 2 - 5 x 7 / 6 x 7
B = 42/42 - 35/42
B = 7/42
B = 7 x 1 / 7 x 6
B = 1/6

C = 12 x (1/3- 1/6)
C = 12 x (1 x 2 / 3 x 2 - 1/6)
C = 12 x (2/6 - 1/6)
C = 12 x 1/6
C = 12/6
C = 6 x 2 / 6 x 1
C = 2/1
C = 2

D = 12 x 1/3 - 1/6
D = 12/3 - 1/6
D = 12 x 2 / 3 x 2 - 1/6
D = 24/6 - 1/6
D = 23/6


2014-02-24T13:52:35+01:00
A) 3/7x(7/3-5/6)
a) 3/7x(14/6-5/6)
a) 3/7x9/6
a)27/42 ou 9/14

b) 3/7x7/3-5/6
b)21/21-5/6
b)1-5/6
b)6/6-5/6=1/6

c)12x(1/3-1/6)
c)12x(2/6-1/6)
c)12x1/6
c)12/6 ou 2

d)12x1/3-1/6
d)12/3-1/6
d)24/6-1/6
d)23/6